Don't sit on my lunch! - Klein, Abby.; McKinley, John, 1956- (New York : Scholastic, 2005)
When first-grader Freddy decides to try out for peewee hockey, his archenemy and school bully Max decides to also try out for the one slot left on the team.
Keywords: Hockey stories; Sports stories; Bullies -- Juvenile fiction; Schools -- Juvenile fiction